The effects and side‐effects of the EU emissions trading scheme. (15th April 2014) - Laing, Timothy; Sato, Misato; Grubb, Michael; Comberti, Claudia
<x xml:space="preserve">Abstract</x> As many countries, regions, cities, and states implement emissions trading policies to limit CO2 emissions, they turn to the European Union's experience with its emissions trading scheme since 2005. As a prominent example of a regional carbon pricing policy, it has attracted significant attention from scholars interested in evaluating the effectiveness and impacts of emissions trading. Among the key difficulties faced by researchers is isolating the effect of the EU ETS on industry operation, investment, and pricing decisions from other dominant factors such as the financial crisis, and establishing credible counterfactual scenarios against this backdrop. This article reviews the evidence, focusing on two intended effects (emissions abatement and investment in low‐carbon technologies) as well as two side‐effects (profits and price impacts). We find that the EU ETS cut CO2 emissions by 40–80 million t/year on average, or 2–4% of the total capped, while the evidence on innovation and investment impacts is inconclusive. There is strong empirical support for cost‐pass through in electricity (20–100%), in diesel and gasoline (>50%), and some preliminary evidence of pricing power in other industrial sectors. Windfall profits have amounted to billions of Euros, and concentrated in a few large companies. For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.